Rapid Control of Reproductive Behaviour by Locally Synthesised Oestrogens: Focus on Aromatase. (28th October 2013) - Cornil, C. A.; Seredynski, A. L.; de Bournonville, C.; Dickens, M. J.; Charlier, T. D.; Ball, G. F.; Balthazart, J.
Abstract : Oestrogens activate nucleus‐ and membrane‐initiated signalling. Nucleus‐initiated events control a wide array of physiological and behavioural responses. These effects generally take place within relatively long periods of time (several hours to days). By contrast, membrane‐initiated signalling affects a multitude of cellular functions in a much shorter timeframe (seconds to minutes). However, much less is known about their functional significance. Furthermore, the origin of the oestrogens able to trigger these acute effects is rarely examined. Finally, these two distinct types of oestrogenic actions have often been studied independently such that we do not exactly know how they cooperate to control the same response. The present review presents a synthesis of recent work carried out in our laboratory that aimed to address these issues in the context of the study of male sexual behaviour in Japanese quail, which is a considered as a suitable species for tackling these issues. The first section presents data indicating that 17β‐oestradiol, or its membrane impermeable analogues, acutely enhances measures of male sexual motivation but does not affect copulatory behaviour. These effects depend on the activation of membrane‐initiated events and local oestrogen production. The second part of this review discusses the regulation of brain oestrogen synthesis through post‐translational modifications of the enzyme aromatase. Initially discovered in vitro, these rapid and reversible enzymatic modulations occur in vivo following variations in the social and environment context and therefore provide a mechanism of acute regulation of local oestrogen provision with a spatial and time resolution compatible with the rapid effects observed on male sexual behaviour. Finally, we discuss how these distinct modes of oestrogenic action (membrane‐ versus nucleus‐initiated) acting in different time frames (short‐ versus long‐term) interact to control different components (motivation versus performance) of the same behavioural response and improve reproductive fitness.